(untitled) (TAMADDUN NURI JURNALI, 2024)
This article is about the different manifestations of deepfakes in media space, the technologies of distribution, types and damage and consequences. Also, on the surface of this article, The opinions presented in the world scientific literature are summarized and suggestions and recommendations are presented.